Doctor Drone: Non-invasive Measurement of Humpback Whale Vital Signs Using Unoccupied Aerial System Infrared Thermography - Horton, Travis W.; Hauser, Nan; Cassel, Shannon; Klaus, K. Frederika; Fettermann, Ticiana; Key, Nicholas (Frontiers in Marine Science, 2019)
Measuring and monitoring the behavior and biomedical condition of free-ranging whales remains a fundamental challenge in cetacean science and conservation. Advances in unoccupied aerial systems (UAS) and infrared thermography (IRT) create unprecedented opportunities to fill these knowledge gaps and advance our understanding of how cetaceans interact with the environment. Here, we show that non-invasive UAS-IRT systems, deployed from shore-based positions in a humpback whale (Megaptera novaeangliae) calving ground, can be used to document rarely observed whale behaviors and to quantify biomedical vital signs, including blowhole and dorsal fin skin temperature, respiration rate, and heart rate. Our findings demonstrate: (1) prolonged (>3 h) logging behavior by a mother-calf pair located ∼550 m offshore; (2) that the calf’s respiration rate (∼3 breaths per minute) was six times higher than its mother’s (∼0.5 breaths per minute); (3) that the calf’s blowholes were ∼1.55°C warmer than adjacent ocean water and that the mother’s blowholes were ∼2.16°C warmer than adjacent ocean water; (4) that the mother’s dorsal fin included four infrared (IR) hot-spots, each separated by ∼20 cm in horizontal distance, that ranged between 1 and 2°C warmer than adjacent ocean water; (5) a significant (p <<0.05; wavelet analysis) temporal cyclicity in the hottest of the mother’s dorsal fin hot-spots consistent with cardiovascular blood flow pumped at an apneic heart rate of ∼9.3 beats per minute. Despite these novel results, there remain several key limitations to UAS-IRT, including its: sensitivity to environmental conditions and animal behavior; equipment costs and associated risks; potential regulatory restrictions; time-intensive nature of IR data processing; factors that can impact data quality, such as imaging angle and sensor accuracy. Future opportunities created by the UAS-IRT results we report center on the potential to couple non-invasive behavioral and physiological monitoring tools, quantify cetacean response to prolonged environmental change and acute disturbances, and extend UAS-IRT applications to cover a wider range of environmental and behavioral contexts. Considering the small sample size of the dataset we report, application of UAS-IRT to live-stranded and captive cetaceans, where environmental and cetacean conditions can be independently measured, is of paramount importance.